2019
DOI: 10.5812/jhealthscope.85622
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxidative Stress Levels in Workers Exposed to Respirable Crystalline Silica in the West of Iran

Abstract: Background: Occupational exposure to crystalline silica is still an important health problem, especially in developing countries. Exposure to silica may be associated with the induction of toxic oxidative stress. Objectives: This study was conducted to assess oxidative stress biomarkers in workers exposed to respirable crystalline silica (RCS) in Hamadan city, the west of Iran. Methods: This descriptive-analytical study was conducted on two groups of exposed workers selected from four industries and unexposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…In the present study, the concentrations of SOD and CAT in the exposed group were significantly higher than the non-exposed group. Similar studies have showed that the levels of SOD and CAT were higher in workers exposed to noise (77–99 dB) (Hosseinabadi et al, 2019); and among workers exposed to silica (Farokhzad et al, 2019; Özgüner et al, 1999). Increased levels of CAT and SOD represent an increase in oxidative stress; in fact, such enzymatic antioxidants are activated in response to the overproduction of free radicals.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the present study, the concentrations of SOD and CAT in the exposed group were significantly higher than the non-exposed group. Similar studies have showed that the levels of SOD and CAT were higher in workers exposed to noise (77–99 dB) (Hosseinabadi et al, 2019); and among workers exposed to silica (Farokhzad et al, 2019; Özgüner et al, 1999). Increased levels of CAT and SOD represent an increase in oxidative stress; in fact, such enzymatic antioxidants are activated in response to the overproduction of free radicals.…”
Section: Discussionmentioning
confidence: 59%
“…This decrease may be because of eliminating the free radicals that are generated by oxidizing agents (cement dust, silica, and noise) in the exposed group (Balbi et al, 2018; Rani and Mythili, 2014). However, in Malekirad’s study at a cement plant (Malekirad et al, 2019), and another similar study on workers exposed to silica, TAC levels were not significantly different in the exposed and non-exposed groups (Farokhzad et al, 2019). The reason for the insignificant difference in the level of TAC among exposed and non-exposed groups in our study and other studies could be due to the indirect effect of oxidative agents on the level of TAC.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, the amounts of SOD and CAT in the exposed group were signi cantly higher than the non-exposed group. Similar studies have showed that SOD and CAT were higher in workers exposed to noise (77-99 dB) [49]; and among workers exposed to silica [34,47]. [50].…”
Section: Discussionmentioning
confidence: 64%
“…The serum level of AST and ALT enzymes are used to evaluate liver function. The liver is the most important organ for cleansing the body from various toxins.AST accumulates in damaged organs including the liver, skeletal muscles, heart and kidney [52,53].Similar studies done in cement factories have shown an increase in AST levels in groups exposed to cement compared to the non-exposed groups as well [33,40,47].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation